Financial assessment of the implementation of state policy measures in the field of environmental protection: macroeconomic aspect - N. N. Shkolnikova; E. A. Shkolnikov; M. A. Shkolnikov (Вестник университета, 2024)
In the current article, financial aspects of the state environmental policy in Russia at the present stage are observed. The authors study the scale of financial resources allocated for environmental protection at the macroeconomic level in the context of ensuring environmental safety. The review of periodical press materials allowed us to highlight the most pressing issues of eco-investment. When processing statistical data to conduct an analysis of the costs of implementing environmental measures and assessing dissipation of funds in the main categories of expenses, the authors used dyna mic and structural methods of economic analysis with determination of absolute and relative difference. A comparative method was implied in comparing retrospective information to monitor annual budget allocations for the needs of ecology alongside with the table method combined with the graphical one. The assessment of expenditures for environmental protection in Russia for 2017–2021 showed an annual stable growth with an almost twofold increase in the whole five years. A structural analysis in the context of environmental protection activities allowed us to identify the dominant cost items as the most significant in the implementation of state environmental policy. A comparative analysis of the unit costs of environmental protection in percentage of gross domestic product through international comparisons indicates the underfunding of this area by Russian state authorities. The limited amount of finance to ensure rational use of natural resources requires implementing principal measures in accordance with the main priorities of state policy in the field along with application of the most effective ecological and economic tools.